Epidemiologia do patossistema Triticum aestivum - Pyricularia oryzae - Silva, Alieze Nascimento da (2021)
Wheat blast caused by the fungus Pyricularia oryzae triticum (PoT), is one of the main limiting factors for wheat cultivation in Brazil. One of the main difficulties related to the control of the disease is related to the gaps in knowledge about its epidemiology. These include issues such as how much PoT is being disseminated in the country via seeds, how long it can saprophytically survive in wheat straw, and the importance of intermediate host plants, such as plants of the genus Urochloa (formerly Brachiaria). The objective of the present work was: (a) to evaluate the importance of seeds, wheat straw and plants of the genus Urochloa as inoculum sources for wheat blast in Brazil and (b) to verify the relationship between PoT infection rates in seeds of wheat and levels of quantitative variables linked to the establishment and health of seedlings. The work was conducted at Embrapa Trigo, Passo Fundo, RS. Four hundred and one wheat seed samples collected in 2017, 2018 and 2019, in the states of GO, MG, MS, PR and RS were subjected to cultural (Blotter Test) and molecular (PCR - Polymerase Chain Reaction) detection procedures . The saprophytic survival of PoT was evaluated in three locations, Londrina (PR), Planaltina (DF) and Uberaba (MG). In the 2018 and 2019 harvests, wheat seed samples were collected in Londrina (PR), Patos de Minas (MG), Uberaba (MG), and 66 samples of forage plant leaves that presented symptoms attributed to blast, whose detection was confirmed via wet chamber and PCR. The presence of PoT was observed in 28.2% of the 401 samples collected in the states of RS, PR, MG, GO and MS, showing the presence of the pathogen in wheat seed samples, and whose molecular detection via PCR allowed amplification in samples with 0.5% incidence of the pathogen. The emergence rates, pathogen incidence, presence of symptoms, mortality, abnormality and transmissibility in wheat seedlings are related to the PoT infection rate in seeds. The pathogen can survive in wheat plants for a period of up to 160 days, in Brazilian subtropical and tropical conditions. Plants of the Urolchoa genus have a natural incidence of the pathogen. The results obtained allow a better understanding of several aspects related to the survival and dissemination of PoT in the Brazilian conditions of occurrence of wheat blast.